Misuse of emergency powers and its effect on civil society—the case of Hungary - Mészáros, Gábor (Frontiers in Political Science, 2024)
Democratic tolerance has been used for their own destruction in Hungary. Gradually, various forms of crisis management have become the very nature of the governing political parties since 2010. Under the framework of Carl Schmitt's enemy-friend dichotomy, the Orbán regime has created its own 'enemies' partially among those who would never be thought to be a threat to a constitutional democracy but to be considered its foundational elements (political opposition, NGOs, free media, etc.). This article shows how emergency powers and autocratic legalism were misused against civil society. There is one simple goal for the Hungarian autocratic regime: defending 'our democracy' against 'them,' who would still like to promote liberal democracy and the rule of law. It is not unique that autocratic techniques conducted with legislation were used against civil society. In Poland, it took two years to subordinate civil society through legislation, and two institutions were created to centralize state control over funds for NGOs (Sadurski 2018). Of course, the Hungarian Parliament, with the supermajority of the Government within, also used legislation to control civil society. However, the way it did it is more different from the Polish case. The abuse of emergency powers began in 2015 by passing emergency measures as seemingly ordinary, quotidian legislation; this process ultimately culminated in a permanent state of exception by 2024. Therefore, we should discuss a permanent emergency where the so-called exception has become the norm and temporary powers endure. After the 'autocratic revolution' (Scheppele 2015), the Hungarian Government pursued a combination of emergency measures and rule by law. As such, the law was manipulated into an instrument of government action (Tamanaha 2004). This approach resulted in a situation where rather than upholding the rule of law and protecting the rights of individuals, legislation serves the government's interests and helps the government to deal with its 'enemies'.